Splice intervals of ODP Site 138-847 - Heather L Ford; Mitchell W Lyle (PANGAEA, 2025)
Here we present an updated age model for ODP Site 138-847. This work builds on the work of Lyle et al. (2019, doi:10.5194/cp-15-1715-2019). This dataset is the splice table for ODP Site 847 B, C and D.